Developmental expression of the potassium current I(K,n) contributes to maturation of mouse outer hair cells - Marcotti, Walter (Blackwell Science Inc, 1999)
1. The expression of K(+) currents in mouse outer hair cells (OHCs) was investigated as a function of developmental age between postnatal day (P) 0 and P26, using whole-cell patch clamp. 2. During the first postnatal week, a slow outward K(+) current (I(K,neo)) was expressed by all OHCs from the apical coil of the cochlea. The amplitude of this current increased greatly between P0 and P6. Then, at the beginning of the second postnatal week, I(K,neo) decreased. At the same time, from P8 onwards, I(K,n), a K(+) current characteristic of mature OHCs, was rapidly expressed. 3. The expression of I(K,n) coincided with the onset of electromotility of the cell body of the OHCs, which could also be detected from P8 onwards and increased substantially in size thereafter. 4. I(K,n) was reversibly blocked by linopirdine, an inhibitor of members of the KCNQ family of K(+) channels, with a K(D) of 0.7 μM. In the cochlea, KCNQ4 is only expressed in OHCs and is responsible for a form of non-syndromic autosomal dominant deafness. Linopirdine had no effect on other OHC K(+) currents at concentrations up to 200 μM. We conclude that ion channels underlying I(K,n) contain the KCNQ4 subunit. 5. In current clamp, depolarizing current injections from the resting potential triggered action potentials in OHCs during the first postnatal week. Thereafter, more rapid and graded voltage responses occurred from more negative resting potentials. Thus, OHCs mature rapidly from P8 onwards, and I(K,n) contributes to this maturation.